2022
DOI: 10.3390/ijms232112716
|View full text |Cite
|
Sign up to set email alerts
|

Poloxam Thermosensitive Hydrogels Loaded with hFGF2-Linked Camelina Lipid Droplets Accelerate Skin Regeneration in Deep Second-Degree Burns

Abstract: Burn injuries are difficult to manage due to the defect of large skin tissues, leading to major disability or even death. Human fibroblast growth factor 2 (hFGF2) is known to promote burn wound healing. However, direct administration of hFGF2 to the wound area would affect the bioactivity. To provide a supportive environment for hFGF2 and control its release in a steady fashion, in this research, we developed novel thermosensitive poloxam hydrogels delivered with hFGF2-linked Camelina lipid droplets (CLD-hFGF2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The bandage made from the formulation also showed a reduction in the amount of exudate as well as macrophage proliferation. Afrin et al [ 57 ] and Zhang et al [ 58 ] also confirmed the efficiency of hydrogels in the wound healing process in an in vivo study. The anti-inflammatory action observed in the results was attributed to flavonols (specifically rutin) present in the calendula extract.…”
Section: Resultsmentioning
confidence: 83%
“…The bandage made from the formulation also showed a reduction in the amount of exudate as well as macrophage proliferation. Afrin et al [ 57 ] and Zhang et al [ 58 ] also confirmed the efficiency of hydrogels in the wound healing process in an in vivo study. The anti-inflammatory action observed in the results was attributed to flavonols (specifically rutin) present in the calendula extract.…”
Section: Resultsmentioning
confidence: 83%
“…Zhang et al encapsulated camelina lipid droplet (CLD)-hFGF2 in thermosensitive hydrogels. 190 The poloxamer composite hydrogels were synthesized from P188 and P407. The shell of these spherical micelles consists of a polyoxyethylene nucleus and an expanded polyoxyethylene chain.…”
Section: Thermosensitive Hydrogel For Diverse Woundsmentioning
confidence: 99%